Avian agnosia: A window into auditory semantics. (November 2019) - Mole, J.A.; Baker, I.W.; Ottley Munoz, J.M.; Danby, M.; Warren, J.D.; Butler, C.R.
Abstract: The functional and neural organisation of auditory knowledge is relatively poorly understood. The breakdown of conceptual knowledge in semantic dementia has revealed that pre-morbid expertise influences the extent to which knowledge is differentiated. Whether this principle applies to a similar extent in the auditory domain is not yet known. Previous reports of patients with impaired auditory vs. intact visual expert knowledge suggest that expertise may have differential effects upon the organisation of auditory and visual knowledge. An equally plausible alternative, however, is that auditory knowledge is simply more vulnerable to deterioration. Thus, expertise effects in the auditory domain may not yet have been observed because knowledge of auditory expert vs. non-expert knowledge has yet to be compared. We had the opportunity to address this issue by studying SA, a patient with semantic dementia and extensive pre-morbid knowledge of birds. We undertook a systematic investigation of SA's auditory vs. visual knowledge from matched expert vs. non-expert categories. Relative to a group of 10 age, education and IQ matched bird experts, SA showed impaired auditory vs. intact visual avian knowledge, despite intact basic auditory perceptual abilities. This was explained by independent effects of modality and expertise. Thus, he was also disproportionately impaired for auditory vs. visual knowledge of items from non-expert categories. In both auditory and visual modalities, his performance was relatively more impaired on tests of non-expert vs. expert knowledge. These findings suggest that, while auditory knowledge may be more vulnerable to deterioration, expertise modulates visual and auditory knowledge to a similar extent. Highlights: Selective preservation of knowledge in a bird expert with semantic dementia. Impaired auditory vs. intact visual avian knowledge. However, performance better for auditory and visual expert vs. non-expert knowledge. First demonstration that expertise protects against loss of auditory knowledge.